EVALUATION OF THE IMPLEMENTATION OF TEACHER PROFESSIONAL EDUCATION IN INDONESIA - AFRIADI, BAMBANG; Tola, Burhanuddin; Devi Triana, Dinny (International Education Trend Issues, 2022)
This research aims to answer and know the implementation of PPG (Pendidikan Profesi Guru /Teacher Professional Education) from various places by studying similar research results. The method used to assess some of the research results using an evaluation approach is the matching method. The matching method is done by matching and comparing the characteristics of the land with the criteria so that one particular conclusion is obtained. Furthermore, a systematic review is used as a Narrative systematic review to review relevant studies. The discussion results resulted in that given the importance of the role of a teacher to improve the quality of Indonesian education, and teachers need to be prepared in such a way as to become professional teachers, one way is to follow PPG. Professional teachers can only pursue the quality of education. Implementing the Teacher Professional Education Program (PPG) is a form of embodiment of Law No. 20 of 2003.